Evaluation of Age-Sex Data Collected in the 1991, 2001 and 2011 Population and Housing Censuses of Namibia - Shipanga, Immanuel; Shinyemba, Tobias (Asian Journal of Population Sciences, 2023)
This paper examined the accuracy of age-sex data reported in the Namibia population censuses with the aim to establish patterns and trends in the quality of age-sex reporting. To date, Namibia has conducted three population and housing censuses. However, it is not clear if there has been any advancement in the quality of data collected on age and sex over the years. The study followed a cross-sectional study design using the 1991, 2001 and 2011 population censuses data from Namibia Statistics Agency. We computed Whipple’s and Myers’s Blended indexes to measure age heaping. The age-sex ratio and UN joint score were used to ascertain the possibility of population undercounts and displacement between age groups. The results show that age heaping was fairly accurate in all three censuses. Analysis of single-age distribution showed a minimal digit preference and avoidance across all three censuses. Likewise, Myers blended index portrayed that terminal digits 0, 1, 2, 5, 8 and 9 were preferred the most by both sexes in all three censuses. The Whipple’s Index showed a two-point decline from 106 in 1991 to 104 in 2001 and 2011 suggesting an improvement in age reporting. The UN joint score for Namibia found that the data collected in all three censuses were inaccurate in terms of age-sex displacement.